Spare embryos and human embryonic stem cell research: ethics of different public policies in the western world - Islam , Sharmin; Nordin, Rusli; Ab. Rani, Samsuddin; Mohd. Nor, Hanapi (The Faculty of Medicine, International Islamic University Malaysia, 2005)

(untitled)
In 1998 scientists discovered in that human embryonic stem cell (HESC) could be derived from human embryos which were created in the laboratory as part of IVF technique. It gives substance to hopes for novel principles of treatment and it is a great project in the biomedicine for the 21st century. But at the same time it triggers serious controversies on significant ethical, social, legal and policy challenges. Different countries have been apt to review their policies regarding this issue and as such a flood of legislations has ensued with the announcement of successful stem cell derivation. The present article seeks to identify the major policy options that have been adopted by the Western world and to examine how ethically their policies sound is. In this paper, we shall try to show how stem cell research can stand the test of different Bioethical principles of Autonomy, Beneficence,Nonmaleficence and Justice (although the principle of Justice will have significance in a narrower sense). The Bioethical theories of Deontology and Consequentialism will also have proper weight. Ultimately we shall defend stem cell research within a certain limit which is a new frontier in Biomedicine.